The application of laser-induced breakdown spectroscopy in domestic detergent residues detection. Issue 108 (20th October 2015) - Zhao, Xiande; Dong, Daming; Zheng, Wengang; Jiao, Leizi; Han, Pengcheng
Abstract : With the increasingly wide application of detergents, the hazards of detergent residues have gained extensive attention. Abstract : With the increasingly wide application of detergents, the hazards of detergent residues have gained extensive attention. The paper aims to explore the application of LIBS (Laser-Induced Breakdown Spectroscopy) in the detection of detergents. In the study, three materials (porcelain, stainless steel, and bamboo) were used as the carrier of detergents and their LIBS spectra were acquired and analyzed. Four brands of detergents that are commonly used in Chinese family were used in the experiment. In the analysis of detergent spectra, the compositions were identified according to emission lines and the elements of Ca, Na, C, H and N were found in detergents. The emission lines of CN and Na were significant and representative and could be utilized to develop rapid detecting system. After detergents were diluted by 2000 times, the characteristic spectral lines of Na at 568.82 nm and 616.22 nm were still measured, which indicates that the method could detect the detergent residues as low as 35.4 μg cm −2 . The spectral characteristics were further studied using chemometrics method and it is demonstrated that there are obvious differences among the samples with different concentrations of detergent. Furthermore, we studied the matrix effects and found the spectral features were not influenced by the carrier materials. It is demonstrated that LIBS is an effective method to detect detergent residues on dishware and its detection limit meets FDA (U.S. Food and Drug Administration) requirements.